An integrative monograph of Carex section Schoenoxiphium (Cyperaceae) - Luceño, Modesto (PeerJ, 2021)
Carex section Schoenoxiphium (Cariceae, Cyperaceae) is endemic to the Afrotropical biogeographic region and is mainly distributed in southern and eastern Africa, with its center of diversity in eastern South Africa. The taxon was formerly recognized as a distinct genus and has a long history of taxonomic controversy. It has also an important morphological and molecular background in particular dealing with the complexity of its inflorescence and the phylogenetic relationships of its species. We here present a fully updated and integrative monograph of Carex section Schoenoxiphium based on morphological, molecular and cytogenetic data. A total of 1,017 herbarium specimens were examined and the majority of the species were studied in the field. Previous molecular phylogenies based on Sanger-sequencing of four nuclear and plastid DNA regions and RAD-seq were expanded. For the first time, chromosome numbers were obtained, with cytogenetic counts on 44 populations from 15 species and one hybrid. Our taxonomic treatment recognizes 21 species, one of them herein newly described (C. gordon-grayae). Our results agree with previous molecular works that have found five main lineages in Schoenoxiphium. We provide detailed morphological descriptions, distribution maps and analytical drawings of all accepted species in section Schoenoxiphium, an identification key, and a thorough nomenclatural survey including 19 new typifications and one nomen novum.